DNA Methylation Patterns in CD8+ T Cells Discern Psoriasis From Psoriatic Arthritis and Correlate With Cutaneous Disease Activity - Charras, Amandine; Garau, Jessica; Hofmann, Sigrun R.; Carlsson, Emil; Cereda, Cristina; Russ, Susanne; Abraham, Susanne; Hedrich, Christian M. (Frontiers in Cell and Developmental Biology, 2021)
Background: Psoriasis is a T cell-mediated autoimmune/inflammatory disease. While some patients experience disease limited to the skin, others develop joint involvement (psoriatic arthritis/PsA). In the absence of disease- and/or outcome-specific biomarkers, and as arthritis can precede skin manifestations, diagnostic and therapeutic delays are common and contribute to disease burden and damage accrual. Objective: Altered epigenetic marks, including DNA methylation, contribute to effector T cell phenotypes and altered cytokine expression in autoimmune/inflammatory diseases. This project aimed at the identification of disease-/outcome-specific DNA methylation signatures in CD8+ T cells from patients with psoriasis and PsA. Method: Peripheral blood CD8+ T cells from 9 healthy controls, 10 psoriasis and 7 PsA patients were collected to analyze DNA methylation marks using Illumina Human Methylation EPIC BeadChips. Bioinformatic analysis was performed using R (minfi, limma, ChAMP and DMRcate packages). Results: DNA methylation profiles in CD8+ T cells differentiate healthy controls from psoriasis patients (397 Differentially Methylated Positions/DMPs; 9 Differentially Methylated Regions/DMRs) when ≥CpGs per DMR were considered; 2 DMRs for ≥10 CpGs). Furthermore, patients with skin psoriasis can be discriminated from PsA patients (1861 DMPs, 20 DMRs (≥5 CpGs per region), 4 DMRs (≥10 CpGs per region)). Gene ontology (GO) analyses considering genes with ≥1 DMP in their promoter delivered methylation defects in skin psoriasis and PsA primarily affecting the BMP signaling pathway and endopeptidase regulator activity, respectively. GO analysis of genes associated with DMRs between skin psoriasis and PsA demonstrated an enrichment of GABAergic neuron and cortex neuron development pathways. Treatment with cytokine blockers associated with DNA methylation changes (2372 DMPs; 1907 DMPs within promoters, 7 DMRs (≥5 CpGs per regions)) affecting TGF receptor and transmembrane receptor protein serine/threonine kinase signaling pathways. Lastly, a methylation score including TNF and IL-17 pathway associated DMPs inverse correlates with skin disease activity scores (PASI). Conclusion: Patients with skin psoriasis exhibit DNA methylation patterns in CD8+ T cells that allow differentiation from PsA patients and healthy individuals, and reflect clinical activity of skin disease. Thus, DNA methylation profiling promises potential as diagnostic and prognostic tool to be used for molecular patient stratification towards individualized treatment.